Elucidating the Complex Interactions between Stress and Epileptogenic Pathways. (21st February 2011) - Friedman, Aaron R.; Cacheaux, Luisa P.; Ivens, Sebastian; Kaufer, Daniela
Abstract : Clinical and experimental data suggest that stress contributes to the pathology of epilepsy. We review mechanisms by which stress, primarily via stress hormones, may exacerbate epilepsy, focusing on the intersection between stress-induced pathways and the progression of pathological events that occur before, during, and after the onset of epileptogenesis. In addition to this temporal nuance, we discuss other complexities in stress-epilepsy interactions, including the role of blood-brain barrier dysfunction, neuron-glia interactions, and inflammatory/cytokine pathways that may be protective or damaging depending on context. We advocate the use of global analytical tools, such as microarray, in support of a shift away from a narrow focus on seizures and towards profiling the complex, early process of epileptogenesis, in which multiple pathways may interact to dictate the ultimate onset of chronic, recurring seizures.